The effect of intercropping of maize with pigeonpea on grain yield and pigeonpea fuelwood supply in Kongwa District, Tanzania - Jonas, Elvis Fahamu (Sokoine University of Agriculture, 2017)
Knowledge on extent to which alternate cropping arrangements may affect yields of both maize and pigeonpeas and fuelwood production from pigeonpeas is important for maximization of outputs. Field experiments were conducted during the 2015 and 2016 periods in Mlali and Chitego Villages, Kongwa District, Dodoma, Tanzania, to assess the effect of intercropping arrangements on the grain yields of maize and pigeonpeas and pigeonpeas fuelwood supply in semi-arid environments. The intercropping arrangements tested were various ratios of maize and pigeonpeas: 1MM: 1PP, 1MM: 2PP, and 2MM: 1PP row proportions, and in their monocultures. Maize grain yields at 1MM: 1PP ratio for the two seasons averaged 0.7 t/ha for Mlali and 1.41 t/ha for Chitego. The increase was 39% higher (27-57%) than mean yield at pure maize (maize monoculture). Maize yield at Chitego during the 2015 (2.49 t/ha) and 2016 (2.89 t/ha) growing season were 62% and 56% higher than the corresponding yields at Mlali. The LER during the 2015 season was highest at 1MM: 2PP ratio in Mlali (1.32) and at 2MM: 1PP ratio in Chitego (1.56). On the other hand LER at 1:1 ratio was intermediate during the 2015 season but the highest (1. 46 and 1. 53) during the 2016 cropping season. Although intercropping reduced yields of sole crops, LER at 1:1 in the 2016 season suggests that in a good year, farmers will benefit more by adopting the alternate intercropping partner. These results suggest that the 1MM: 1MM ratio could be adopted for wider use by farmers in the two sites. Overall the LER results affirm that farmers diversifying crop production by intercropping will benefit more even in seasons of uncertain crop production like the 2015 season. It is recommended that farmers who wish to grow maize and pigeon pea should grow them in association with maize by adopting the alternate intercropping partner 1MM: 1PP cropping arrangements as it provide more benefit.